PENGARUH IKLAN DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PRODUK SIMPATI (Studi Pada Pengguna Kartu Simpati di Wilayah Kota Malang Jawa Timur) - Muhamad Bilal; Fatchur Rohman (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This study aims to determine the effect of Advertising and Product Quality Consumer Purchase Decision Against Simpati Product (Studies in Simpati Card Users in Malang district of East Java). Types of research used in this research is explanatory research (research explanation) that aims to explain the causal relationship between the causal variables through hypothesis testing. Data were collected through a questionnaire survey to Simpati card users in the city of Malang. The sampling technique used was purposive sampling and obtained a sample of 60 respondents. To test the hypothesis proposed in this study used regression analysis. Regression analysis showed that advertising and product quality as well as partial simultaneously have a significant influence on purchasing decisions. Between the two variables, variables which have a dominant influence on purchasing decisions is advertising variable. Based on this analysis, suggestions are given in the advertisement Simpati seatraktif delivery must be made possible to be able to attract the attention of consumers, delivery time and location of ad placements should be tailored to the target of the ad, and use resources more messages are generally not accepted by the or some circles only. Meanwhile, in terms of the quality of the following suggestions should be used as a consideration which, always present things that are new and innovative for consumers, and provide packages attractive prices and promotions are tailored to the needs of consumers. Keywords: advertising, product quality, and purchase decision